Analysis of Students' Mathematical Misconceptions in Solving Contextual Problems in Fractional Number Material - Nurma Izzati; Siska Zahara (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to describe the forms of mathematical misconceptions of students in solving contextual problems in fractional number material. The research used a descriptive qualitative approach and was carried out at SD Negeri 1 Gandasoli, Kuningan Regency. The subjects of the study were all students of class V totaling 39 people. Data was obtained through a written test in the form of contextual description questions about fractional numbers that have gone through the validity test stage. Based on the test results, students were classified into three levels of mathematical ability, namely high, medium, and low, then 9 students were selected as sample subjects for in-depth analysis. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that students still experience various types of mathematical misconceptions, including misconceptions of translation, signs, calculations, systematic, concepts, and strategies. Misconceptions of translation and signs were found at all levels of mathematical ability, while calculating, systematic, and conceptual misconceptions appeared in students of medium and low ability. Strategic misconceptions are only found in students with low mathematical ability. These findings show that the complexity of misconceptions increases as students' mathematical ability levels decrease, so learning that emphasizes understanding concepts and meaningful problem-solving in fractional number material is needed.